PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET SERTA IMPLIKASINYA TERHADAP HARGA SAHAM PADA PT JAPFA COMFEED INDONESIA TBK PERIODE 2013-2023 - Widyastuti, Dinta Febby; Ludvy, Achmad (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect Current Ratio and Debt To Equity Ratio on Return On Assets and its implications for Share Prices at PT Japfa Comfeed Indonesia Tbk for the 2013 - 2032 period. The population and sample in this study used the Financial Report of PT Japfa Comfeed Indonesia Tbk from 2013 to 2023. The research method used was a quantitative descriptive method. The data used is secondary data. The analytical methods used are descriptive statistical tests, classical assumption tests, multiple regression analysis, simple linear regression analysis, coefficient of determination analysis, correlation coefficient analysis, and hypothesis testing using t test and F test. The results obtained, the Current Ratio has not significant effect on Return On Assets. The Debt To Equity Ratio has a significant negative effect on Return On Assets. Third, simultaneously the Current Ratio and Debt To Equity Ratio have an effect but not significant on Return On Assets. Fourth, Return On Assets has a significant effect on Stock Prices.